The internal audit of the quality management system in a medical devices distributor: a case study (Research, Society and Development, 2021)
The medical devices market is a sector in which regulatory agencies exert great pressure on quality control and management, in order to prevent damage to individual and collective health. Thus, internal audits are seen as fundamental for monitoring and improving the quality of products, services and quality management systems (QMS). The present study, carried out between January and February 2021, aimed to investigate the impact of AUDIN on the maintenance and improvement of the QMS of a healthcare products distributor located in Salvador/BA. It was observed that the QMS of the case under analysis follows the parameters defined by RDC 16/2013, with the AUDIN results as guidelines for promoting the PDCA cycle. Non-conformities (NC) were identified in 8% of the audited requirements, all with the development of an action plan, survey of corrective and preventive measures and evaluation of effectiveness, showing 60% and 80% effectiveness, after seven and twenty days, respectively, from which it is concluded that AUDIN showed great effectiveness for the detection and correction of NC in the QMS, helping to prevent damage to the individual and collective health of users.